iKEN 3D environment mobile application / Else Scully Geoffry … [et al.] - Geoffry, Else Scully; Juslin, Nurgayah; Jalius, Kasliani; Said, Ibrahim; Johnny, Cindy (Faculty of Computer and Mathematical Sciences, 2022)
iKEN app is a mobile application that maximizes tourists’ experiences when traveling to destinations, especially historical destinations. The iKEN app uses a 3D environment commonly used in Virtual Reality (VR) technology, except it was used in mobile phones. Although tourists may grasp some of the historic building's past conditions through browsing pictures on the web, the iKEN app can create a better experience and easier access to historical conditions and environments. The iKEN app allows users to access targeted historical buildings from any era. The information about these buildings is gathered from the experts on that destination. Applying 3D modelling to the targeted destination helps tourists observe the area from any angle. Thus, by using this application, tourists can access the information of targeted goals, such as historical information, without searching it from various resources on the web. Moreover, this application is convenient for tourists that love to travel solo as the tourists still manage to access the information without the help of a tour guide. The benefit of this iKEN app is its ease of information access to the history of the places, increasing knowledge, and creating a whole other level of experience. The methodology or method used in developing the iKEN apps is the agile method. The agile method focused on improvement to be of better quality. In conclusion, the iKEN app helps maximize tourists’ knowledge and experiences when visiting historical destinations and creates a new level of tourism innovation.